DIAGNOSTICS AND TREATMENT OF PULMONARY MYCOBACTERIOSIS IN THE PATIENTS WITH SUSPECTED PULMONARY TUBERCULOSIS - P. I. Eliseev; А. O. Maryandyshev; I. V. Tarasova; А. Kheldal; S. G. Khinderaker (Туберкулез и болезни лёгких)
.